(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
It was investigated the species composition and especially of distribution the seaweeds in connection with ecological conditions of different areas of Odessa coastal. Was show that lowering of salinity and increasing level of pollution lead to simplification the structure of bottom phytocenosis and reduce their floristic diversity.